Computational modelling of cold-formed steel screwed connections at ambient and elevated temperatures - Mesquita, L.M.R. (2016)
The application of cold-formed steel structural members in steel construction, and in particular building construction, has a number of advantages that includes its high structural efficiency compared to the member weight. In recent years the increasing safety requirements reflected in the different design standards, boosted the behaviour of materials under extreme conditions, in particular in conditions of high temperatures such as those arising from fires. This work presents a study of the behaviour of cold-formed thin steel sheeting screwed connec-tions at room temperature and elevated temperatures. The shear and bearing failure modes are analysed experimentally by means of a parametric analysis, considering: (i) different elevated temperature values; (ii) cold-formed steel grades; (iii) board effect of the screw position; (iv) and different steel sheet thicknesses. The set of experimental results are used for calibration and verification of the numerical model developed by the finite element method in the software An-sys. The experimental tests presented allowed to determine the load resistance of self-drilling screwed connections of thin steel sheets and the influence of the sheet thickness, edge distance (e1) and the connection temperature. The results show that for the same connection, keeping the sheet thickness and edge distance e1, a change on the failure mode with the temperature increase occur. The finite element numerical model presented allow to study the behaviour of self-drilling screwed connections and determine the collapse load. The cases analysed give re-sults close to the characteristic resistance of the screws manufacturer.